14-3-3 protein and ubiquitin C acting as SjIAP interaction partners facilitate tegumental integrity in Schistosoma japonicum. Issue 5 (April 2019) - Liu, Juntao; Giri, Bikash Ranjan; Chen, Yongjun; Cheng, Guofeng
Graphical abstract: Highlights: 14-3-3 protein and ubiquitin C (UBC) interact with an inhibitor of apoptosis protein in Schistosoma japonicum . Inhibition of Schistosoma japonicum 14-3-3 and UBC lead to tegument destruction in parasites. 14-3-3 and UBC might play important roles in maintaining tegument integrity in S. japonicum . Abstract: Schistosomiasis, caused by trematodes of the genus Schistosoma, remains an important public health issue . Adult schistosomes can survive in the definitive host for several decades, although they are subject to the host immune response. Consequently, understanding the mechanism underlying worm survival in the definitive hosts could aid in developing novel strategies against schistosomiasis. We previously found that an inhibitor of apoptosis in Schistosoma japonicum (SjIAP) could negatively regulate apoptosis by inhibiting caspase activity, which plays a critical role in maintaining tegument integrity. The current study aimed to further analyze the mechanism related to SjIAP governing worm tegument integrity; therefore, we used a yeast two-hybrid screen and identified a series of putative interacting partners of SjIAP, including 14-3-3 (Sj14-3-3) and ubiquitin C (SjUBC). Quantitative real time PCR (qRT-PCR) analysis indicated that transcript profiles of Sj14-3 - 3 and SjUBC increased together with worm development in definitive hosts, which corresponds to those of SjIAP in S. japonicum . Immunohistochemical analysis showed Sj14-3-3 and SjUBC were located in the tegument of adult parasites while they were also ubiquitously distributed in the bodies of worms. Silencing of Sj14-3 - 3 / SjUBC expression led to increased caspase activity and induced worm death. Inhibition of Sj14-3-3 or SjUBC resulted in significant morphological alterations in the schistosome tegument. Overall, our findings indicated that Sj14-3-3 and SjUBC interacting with SjIAP may belong to another strategy of S. japonicum to maintain the tegument integrity.